Public environmental awareness and performance in Kuala Lumpur City, Malaysia — a case study on household electrical and electronic equipment - Rafia, Afroz; Masud, Muhammad Mehedi; Akhtar, Rulia; Duasa, Jarita (Sage Publications, 2012)
The aim of this paper is to estimate the perception, knowledge and attitude of the respondents towards electrical and electronic equipment waste (e-waste) management. It also tried to identify current e-waste management practiced by households in Kuala Lumpur. In order to ensure a higher response rate, face-to-face survey was employed. In this study, it has been found that 69 per cent of the respondents were satisfied with Kuala Lumpur’s environmental quality, while 31 per cent were not satisfied. More than one third of the respondents informed that they send their electric and electronic equipment (EEE) to charity or transfer the EEE to relatives if they cannot repair them. Only a small fraction of the used EEE finds its way to recycling facilities and manufacturer as there is no efficient take back scheme for consumers. It has been also found in this study that more than 81 per cent of the respondents are unenthusiastic to pay for the recycling of their e-waste. It is interesting to find that much of the EEE was updated within two thirds of their designed lifetime.